Visceral Leishmaniasis (Kala-azar) in Nepalgunj Medical College - B.K., Shyam Kumar; Bassi, S. D.; Baral, S.; Shah, A.; Dhakal, A. (Journal of Nepalgunj Medical College, 2018)
Background: Visceral leishmaniasis (VL) or Kala-azar is a potentially fatal vector-borne (sand fly phlebotomies spp) zoonotic disease caused by a protozoan parasite, Leishmaniadonovani. Kala-azar remains a public health problem in Nepal. The patient presented with a history of high-grade fever, abdominal distension, anemia, and weight loss. The disease is preventable, but various environmental, socioeconomic, health care and health behavior related variables affect its transmission.Objective: Find out the incidence of Kala-azar infection in Nepalgunj medical college.Method: This Hospital based study. Data was collected from April 2018to August 2018. Blood sample collected and test rk39 performed in laboratory of Nepalgunj Medical College Kohalpur. Result: Among 75 patients 16 were diagnosed kala-azar, rk39 positive 14 males and 2 females respectively. It is 12% of total cases. Among 16cases male are 14 and 2 are females. 85.7% male and 12.3% female. Age group between 15-30 years (31.25%), 31-45 years (25%), 46-60 years(18.75%), 61-75 years (12.5%), 76-85 years (12.5%). young people's age group 15-30 years are commonly infected.Conclusion: Visceral leishmaniasis (kala-azar) cases are still major health problem in Nepal. There should be regular surveillance research work to be carried out in both epidemic and non-epidemic districts of the country. Mass public health education, to make the people aware about preventive aspects of the disease is important.